Fire effects and ecological recovery pathways of tropical montane cloud forests along a time chronosequence. (24th November 2017) - Oliveras, Imma; Román‐Cuesta, Rosa M.; Urquiaga‐Flores, Erickson; Quintano Loayza, Jose A.; Kala, Jose; Huamán, Vicky; Lizárraga, Nohemi; Sans, Guissela; Quispe, Katia; Lopez, Efrain; Lopez, David; Cuba Torres, Israel; et al.
Abstract: Tropical montane cloud forests (TMCFs) harbour high levels of biodiversity and large carbon stocks. Their location at high elevations make them especially sensitive to climate change, because a warming climate is enhancing upslope species migration, but human disturbance (especially fire) may in many cases be pushing the treeline downslope. TMCFs are increasingly being affected by fire, and the long‐term effects of fire are still unknown. Here, we present a 28‐year chronosequence to assess the effects of fire and recovery pathways of burned TMCFs, with a detailed analysis of carbon stocks, forest structure and diversity. We assessed rates of change of carbon (C) stock pools, forest structure and tree‐size distribution pathways and tested several hypotheses regarding metabolic scaling theory (MST), C recovery and biodiversity. We found four different C stock recovery pathways depending on the selected C pool and time since last fire, with a recovery of total C stocks but not of aboveground C stocks. In terms of forest structure, there was an increase in the number of small stems in the burned forests up to 5–9 years after fire because of regeneration patterns, but no differences on larger trees between burned and unburned plots in the long term. In support of MST, after fire, forest structure appears to approximate steady‐state size distribution in less than 30 years. However, our results also provide new evidence that the species recovery of TMCF after fire is idiosyncratic and follows multiple pathways. While fire increased species richness, it also enhanced species dissimilarity with geographical distance. This is the first study to report a long‐term chronosequence of recovery pathways to fire suggesting faster recovery rates than previously reported, but at the expense of biodiversity and aboveground C stocks. Abstract : Burned Tropical Montane Cloud forests show different carbon stock recovery pathways depending on the selected carbon pool and time since last fire. Their forest structure recovers at faster rates than previously reported but at the expense of biodiversity and aboveground carbon stocks.